Time trends in socio-economic, urban-rural and regional disparities in prevalence of obesity among non-pregnant women in Lesotho: evidence from Lesotho demographic and health surveys (2004-2014) - Betregiorgis Zegeye; Gebretsadik Shibre; Gashaw Garedew Woldeamanuel (BMC, 2021)
Abstract Background The growing rates of obesity in developing countries are alarming. There is a paucity of evidence about disparities of obesity in Lesotho. This study examined socioeconomic and area-based inequalities in obesity among non-pregnant women in Lesotho. Methods Data were extracted from the 2004, 2009 and 2014 Lesotho Demographic and Health Surveys (LDHS) and analyzed through the recently updated Health Equity Assessment Toolkit (HEAT) of the World Health Organization. Obesity prevalence was disaggregated by four equity stratifiers, namely education, wealth, residence and sub-national region. For each equity stratifier, simple and complex as well as relative and absolute summary measures were calculated. A 95% confidence interval was used to measure statistical significance of findings. Results We noticed substantial wealth-driven (D = -21.10, 95% CI; − 25.94, − 16.26), subnational region (PAR = -11.82, 95%CI; − 16.09, − 7.55) and urban-rural (− 9.82, 95% CI; − 13.65, − 5.99) inequalities in obesity prevalence without the inequalities improved over time in all the studied years. However, we did not identify educational inequality in obesity. Conclusions Wealth-driven and geographical inequalities was identified in Lesotho in all the studied time periods while education related inequalities did not appear during the same time period. All population groups in the country need to be reached with interventions to reduce the burden of obesity in the country.